Prioritisasi Turunan Aaptamine sebagai Kandidat Antibakteri melalui Analisis Swiss-ADME dan Protox-II - Annisa Elcentia Fajarwati; Diana Andari (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Antimicrobial resistance has driven the urgent need to develop new antibacterial candidates with favorable efficacy, pharmacokinetic properties, and safety profiles. Aaptamine derivatives, secondary metabolites isolated from marine sponges of the genus Aaptos, have demonstrated potential as drug candidates; however, studies evaluating their drug-likeness, Absorption, Distribution, Metabolism, and Excretion (ADME) properties, and toxicity profiles remain limited. This study aimed to prioritize aaptamine, demethyl(oxy)aaptamine, and isoaaptamine as potential antibacterial candidates through SwissADME and ProTox-II analyses using an in silico approach. The results demonstrated that all three compounds satisfied the Lipinski's Rule of Five criteria for drug-likeness, exhibited high gastrointestinal absorption, and achieved a bioavailability score of 0.55. All compounds were predicted to belong to toxicity class 4, with predicted LD₅₀ values of 1300 mg/kg for aaptamine, 500 mg/kg for demethyl(oxy)aaptamine, and 1350 mg/kg for isoaaptamine, while none showed hepatotoxic or cytotoxic properties. The integrated analysis indicated that isoaaptamine exhibited the most balanced drug-likeness, ADME profile, and safety characteristics, making it the highest-priority antibacterial candidate. This study concludes that the integration of SwissADME and ProTox-II provides an effective preliminary approach for screening marine natural product-derived drug candidates. The novelty of this study lies in the integrated application of drug-likeness, ADME, and toxicity analyses to systematically prioritize three aaptamine derivatives, thereby providing a more comprehensive lead compound selection strategy for antibacterial drug discovery.